Plan de negocio para la creación de la empresa Sanguer S.A.S que diseña, produce y comercializa tacones modificables para dama en la ciudad de Santiago de Cali (2016)
The present project of entrepreneurship for the creation of a modified shoe for Lady company, aims to present a detailed analysis of the various technical studies needed to determine the economic viability and possible execution of the project. The market study analyse supply and demand for the product going to market SANGUER S.A.S; who is going to compete and strategies will be used to be more competent in the market. The technical study in addition to determining the technical feasibility of the project we will indicate that type of machinery and equipment, supplies and raw need and applied technology that will be used to develop the product and take it for sale. This study will be the source of relevant information for the realization of the economic and financial study. The administrative and legal study will establish the needs of personnel occupying administrative and operational charges, profile that is required, the types of employment contracts that should be implemented and what will be the management structure (organization chart) of the entity to be formed. In the economic and financial study, we will determine the goodness of the project; This is, if it is feasible or not.